Efficacy of bevacizumab plus irinotecan in children with recurrent low-grade gliomas—a Pediatric Brain Tumor Consortium study. Issue 2 (4th December 2013) - Gururangan, Sridharan; Fangusaro, Jason; Poussaint, Tina Young; McLendon, Roger E.; Onar-Thomas, Arzu; Wu, Shengjie; Packer, Roger J.; Banerjee, Anu; Gilbertson, Richard J.; Fahey, Frederic; Vajapeyam, Sridhar; Jakacki, Regina; et al.
Abstract: Background: A phase II study of bevacizumab (BVZ) plus irinotecan (CPT-11) was conducted in children with recurrent low-grade glioma to measure sustained response and/or stable disease lasting ≥6 months and progression-free survival. Methods: Thirty-five evaluable patients received 2 doses (10 mg/kg each) of single-agent BVZ intravenously 2 weeks apart and then BVZ + CPT-11 every 2 weeks until progressive disease, unacceptable toxicity, or a maximum of 2 years of therapy. Correlative studies included neuroimaging and expression of tumor angiogenic markers (vascular endothelial growth factor [VEGF], VEGF receptor 2, hypoxia-inducible factor 2α, and carbonic anhydrase 9). Results: Thirty-five evaluable patients (median age 8.4 y [range, 0.6–17.6]) received a median of 12 courses of BVZ + CPT-11 (range, 2–26). Twenty-nine of 35 patients (83%) received treatment for at least 6 months. Eight patients progressed on treatment at a median time of 5.4 months (range, 1–17.8). Six patients (17.7%) still in follow-up have had stable disease without receiving additional treatment for a median of 40.1 months (range, 30.6–49.3) from initiating therapy. The 6-month and 2-year progression-free survivals were 85.4% (SE ± 5.96%) and 47.8% (SE ± 9.27%), respectively. The commonest toxicities related to BVZ included grades 1–2 hypertension in 24, grades 1–2 fatigue in 23, grades 1–2 epistaxis in 18, and grades 1–4 proteinuria in 15. The median volume of enhancement decreased significantly between baseline and day 15 ( P < .0001) and over the duration of treatment ( P < .037). Conclusion: The combination of BVZ + CPT-11 appears to produce sustained disease control in some children with recurrent low-grade gliomas.